Optimizing Elementary School Teacher Performance: Integration of Instructional Leadership and Collegial Supervision in an Integrated Supervision Model - Lastria Irianti; Dedy Achmad Kurniady; Sururi Sururi (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
This study examines the combined influence of instructional leadership and collegial supervision on teacher performance, addressing the need for a comprehensive approach that integrates managerial direction with peer-based collaboration. Using a quantitative survey of 300 teachers from 51 public elementary schools in Purwakarta Regency, Indonesia, data were analyzed using Partial Least Squares–Structural Equation Modeling. The findings show that both instructional leadership and collegial supervision significantly and positively affect teacher performance, jointly explaining 18.1 percent of its variance. Collegial supervision was also found to mediate 34.6 percent of the effect of instructional leadership, highlighting its crucial bridging role. The integrated supervision model demonstrated consistent robustness across urban and rural school contexts. The study concludes that combining instructional leadership with collegial supervision creates a synergistic effect that enhances teacher performance more effectively than implementing either approach independently, offering valuable guidance for improving supervision practices in elementary schools.